2018
DOI: 10.1002/cssc.201800052
|View full text |Cite
|
Sign up to set email alerts
|

Gold–Copper Aerogels with Intriguing Surface Electronic Modulation as Highly Active and Stable Electrocatalysts for Oxygen Reduction and Borohydride Oxidation

Abstract: We, for the first time, report the successful synthesis of self-assembled AuCu aerogels by a one-pot kinetically controlled approach. A startling electronic modulation effect of Cu on Au was observed across the entire alloy composition range, for which the optimal upshift of the d-band center for the highest activities was 0.24 eV. Owing to the combination of a nanoporous architecture and a robust electronic effect, the Au Cu aerogels exhibited better catalytic performance for the oxygen reduction reaction (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 60 publications
(53 reference statements)
1
39
0
Order By: Relevance
“…[79] Because of the extreme simplicity, this method has been widely adopted and extended to Au-Cu, Pd-Cu, and Pt-Ni systems. [80][81][82] To reduce the long gelation time required for the one-step method, Lin's group addressed this issue in M-Cu (M = Pd, Pt, and Au) and Au-Pt systems by raising the reaction temperature ( Figure 7c). [74,83] Via one-pot reducing two metal salt precursors by NaBH 4 at 333 K, monolithic hydrogels formed in 2-6 h, displaying moderate SSAs of 21.3-37.5 m 2 g −1 .…”
Section: One-step Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…[79] Because of the extreme simplicity, this method has been widely adopted and extended to Au-Cu, Pd-Cu, and Pt-Ni systems. [80][81][82] To reduce the long gelation time required for the one-step method, Lin's group addressed this issue in M-Cu (M = Pd, Pt, and Au) and Au-Pt systems by raising the reaction temperature ( Figure 7c). [74,83] Via one-pot reducing two metal salt precursors by NaBH 4 at 333 K, monolithic hydrogels formed in 2-6 h, displaying moderate SSAs of 21.3-37.5 m 2 g −1 .…”
Section: One-step Methodsmentioning
confidence: 99%
“…The same authors found that high‐SSA aerogels (73 to 168 m 2 g −1 ) can be also obtained for the Pd–Pt system without the introduction of additives, but a much longer time of 3–17 d was required to acquire hydrogels . Because of the extreme simplicity, this method has been widely adopted and extended to Au–Cu, Pd–Cu, and Pt–Ni systems …”
Section: Fabrication Strategiesmentioning
confidence: 99%
See 3 more Smart Citations